Enterprise Architecture Blueprint: Guna Mencapai Keselarasan Dari Organisasi Dan Teknologi Informasi Dengan Pendekatan Togaf Dan Itil (studi Kasus : Are Fungsi It Planning & Development Pt Bank Pembangunan Daerah Jawa Barat Dan Banten, Bandung) - Firdaus Adi Nugroho; Irfan Darmawan; Asti Amalia Nur Fajrillah (eProceedings of Engineering, 2019)
Abstrak Fungsi IT Planning & Development merupakan salah satu fungsi penting yang terdapat pada Bank BJB. Cakupan IT Planning & Development yang rendah dan tidak sejalan dengan perspektif bidang bisnis menjadi salah satu permasalah utama sehingga tidak sejalannya dan tidak optimal anatara Teknologi Informasi dengan jalannya bisnis. Untuk itu, Untuk menyatukan perspektif antara Teknologi Informasi dan Bisnis diperlukan penerapan suatu sistem, dalam menerapkan sistem makan diperlukan blueprint berbasis layanan perbankan yang digunakan sebagai panduan dalam membangun Teknologi Informasi di perusahaan. Enterprise Architecture merupakan solusi yang dapat digunakan dalam merancang sistem berbasis layanan perbankan di perusahaan dengan mengintegrasikan domain-domain seperti Bisnis, Aplikasi, Data, Teknologi, dan mengadopsi best practice berbasis layanan. TOGAF ADM dapat memenuhi kebutuhan pengembang sistem dengan menyelaraskan keempat domain yang ada pada perusahaan, dan ITIL (Information Technology Infrastructure Library) merupakan best practice sebagai referensi layanan perusahaan. Perancangan Enterprise Architecture berbasis layanan perbankan di dalam penelitian ini menggunakan framework TOGAF ADM yang dikombinasikan dengan ITIL. Membatasi hanya pada perancangan preliminary phase, Phase A : Architecture Vision, Phase B: Business Architecture Kata kunci: Enterprise Architecture, ITIL, Keselarasan perspektif IT dan Bisnis , Domain Abstract IT Planning & Development function is one of the important functions contained in BJB Bank. IT Planning & Development not coverage and not align with the perspective of the business sector become one of the main problems so that it is not align and is not optimal between Information Technology and the course of business. To that end, to unify the perspective between Information Technology and Business, the application of a system is needed, in implementing a food system a banking service-based blueprint is needed which is used as a guide in developing Information Technology in a organization. Enterprise Architecture is a solution that can be used in designing banking service-based systems in companies by integrating domains such as Business, Applications, Data, Technology, and adopting service-based best practices. TOGAF ADM can meet the needs of system developers by aligning the four existing domains in the company, and ITIL (Information Technology Infrastructure Library) is a best practice as a reference for service organization. Banking service-based Enterprise Architecture design in this study uses the TOGAF ADM framework combined with ITIL. Limiting only the design of the preliminary phase, Phase A: Architecture Vision, Phase B: Business Architecture, Phase C: Architecture Information Systems (Data Architecture & Application Architecture), Phase D: Technology Architecture, Phase E: Opportunities and Solutions, and Phase F: Migration Planning without considering Phase G: Implementation Governance and Phase F: Architecture Change Management. Each phase inserts of artefact from ITIL. The outputs of this study are in the form of Enterprise Architecture and IT Roadmap based on banking services as a guide in implementing the system in the BJB Bank's IT Planning & Development function. Keywords: Enterprise Architecture, ITIL, Alignment of perspective between IT and Business